2014
DOI: 10.1038/ijo.2014.114
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hormonal contraceptive use and offspring overweight or obesity

Abstract: Objective Experiments in animal models have shown a positive association between in utero exposure to pharmacologic sex hormones and offspring obesity. The developmental effects of such hormones on human obesity are unknown. Methods Using data from a large, prospective pregnancy cohort study (n=19,652), with linkage to a national prescription registry, we evaluated the association between use of hormonal contraceptives before and after conception (defined from dispensed prescription data and characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…BMI was based on parental reports. A recent article 54 reported the results of a validation study done to assess the accuracy of parental-reported BMI in the MoBa study. The reported BMIs were compared with measured BMIs obtained in the Bergen Growth Study.…”
Section: Discussionmentioning
confidence: 99%
“…BMI was based on parental reports. A recent article 54 reported the results of a validation study done to assess the accuracy of parental-reported BMI in the MoBa study. The reported BMIs were compared with measured BMIs obtained in the Bergen Growth Study.…”
Section: Discussionmentioning
confidence: 99%
“…Jensen et al . () reported that use of the progestin in early pregnancy was positively associated with offspring overweight or obesity. The patients undergoing AID groups in our centre were given conventional luteal support, which may explain the differences between two groups in the distribution of birthweight.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that in utero exposure to obesogens , including various types of endocrine disruptors, can disturb the developmental and homeostatic controls over adipogenesis, thus affecting the weight‐control mechanisms and energy balance later in life . Prenatal exposure to pharmacologic sources of estrogenic agents such as oral contraceptives and diethylstilbestrol were linked to childhood overweight or obesity in a few studies . Acetaminophen has been reported to induce rather strong hormonal effects, such as inhibiting androgen or prostaglandin synthesis, in experimental settings .…”
Section: Discussionmentioning
confidence: 99%